Studi Wacana Radikalisme Di Lingkungan Mahasiswa Bali - Putri, Penny Kurnia; Dharmiasih, D.A Wiwik (Jurnal Ilmiah Widya Sosiopolitika, 2022)
Radicalism has recently become a BIG issue in Indonesia. The government once again resound the vigilance over terrorism since the stabbing of the former Coordinating Minister for Political, Legal and Security Affairs, Wiranto, which occurred on October 10, 2019. The university environment then became one of the educational institutions that were considered vulnerable to being exposed to the spread of this ideology. This study aims to determine the map of student understanding in Bali related to the discourse of radicalism in Indonesia. The analysis was carried out using qualitative methods through questionnaires, group discussions and interviews with students at several universities in Bali. The results showed that most of them (80%) had understood of the context of radicalism in Indonesia, but lacked understanding of the terminology of radicalism scientifically. Only a few students have a critical character in addressing the issue of radicalism and rejecting a single narrative. Furthermore, in general students in Bali are not in a vulnerable position to be exposed to radicalism, although there are pros and cons. In the academic realm, every issue theme deserves to be discussed as long as it does not deviate from the scientific context. A critical view is actually needed as a means of learning, and understanding issues from real scientific sources